Composition for sealing electronic device, film for sealing electronic device, and method for forming film for sealing electronic device
By using (meth)acrylate as the photopolymerizable monomer in the electronic device packaging composition and optimizing its dipole moment, molecular volume and hydrogen bonding parameters, the stability and performance problems of the inkjet packaging film are solved, and a high-performance packaging film is achieved.
Patent Information
- Application Number
- CN202380056660.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-26
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, it is difficult to form an electronic device packaging film based on the inkjet method, and the ejection stability, luminescence characteristics and crack resistance of the packaging film are poor, and the dielectric constant is high.
The electronic device packaging composition containing (meth)acrylate as the photopolymerizable monomer is used to ensure the stability and performance of the encapsulation film by calculating the parameters S1 and S2 within a specific range of the dipole moment, molecular volume and hydrogen bond terms of the photopolymerizable monomer.
An electronic device packaging film with excellent ejection stability, luminescence characteristics and crack resistance based on the inkjet method is realized, and the relative dielectric constant is low, which improves the overall performance of the packaging film.
Smart Images

Figure BDA0005258001370000111 
Figure BDA0005258001370000121 
Figure BDA0005258001370000131
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for encapsulating electronic devices, an electronic device encapsulating film and a method for forming an electronic device encapsulating film, and in particular to a composition for encapsulating electronic devices that can form an electronic device encapsulating film having excellent ejection stability, luminescent properties and crack resistance based on an inkjet method and a low relative dielectric constant. Background Art
[0002] Ink compositions for organic EL thin films for forming thin films such as light-emitting layers of electronic devices, especially organic electroluminescent devices (hereinafter also referred to as "organic EL devices" or "organic EL elements") have been proposed in the past. For example, Patent Document 1 discloses a composition containing an organic EL material, a liquid crystal compound with a band gap of 3.5 eV or more, and a solvent composed of an organic compound as a high-viscosity organic EL ink composition that can be manufactured by an inexpensive printing technology other than the inkjet method. In addition, it is disclosed that the dipole moment of the above-mentioned liquid crystal compound is preferably 4.0 Debye or less. Moreover, it is believed that such an ink composition can be widely used in various coating methods because it has a high viscosity and can maintain high efficiency and long-life luminescent properties.
[0003] In addition, Patent Document 2 discloses a curable resin composition containing a vinyl polymer powder having a glass transition temperature of 120° C. or higher and a mass average molecular weight of 100,000 or higher as a resin composition for use in the electronics field. In particular, it is disclosed that the molar volume of the monomer unit of the vinyl monomer is preferably 150 cm 3 Moreover, it is believed that such a technique can provide a cured product having good dispersibility in a curable resin composition, which can be quickly turned into a gel state by heating for a short time, and has a low linear expansion coefficient and good crack resistance.
[0004] On the other hand, in electronic devices, in order to prevent organic materials and electrodes used from being degraded by moisture, it has been proposed to cover the surface of an organic EL element with a sealing layer.
[0005] However, such an encapsulation layer is required to have no influence on the light-emitting layer of the organic EL element, to have excellent light-emitting properties, and to have excellent crack resistance after curing. In addition, when forming by an inkjet method, it is desired to stably eject the encapsulation composition from the nozzle.
[0006] Furthermore, it is preferred that the material is not easily polarized when an electric field is applied to the electronic device, and that the relative dielectric constant is low.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2010 / 143431
[0010] Patent Document 2: International Publication No. 2013 / 062123 Summary of the invention
[0011] The present invention is made in view of the above problems and situations, and the problem to be solved is to provide a composition for electronic device encapsulation that can form an electronic device encapsulation film having excellent ejection stability, luminescence characteristics and crack resistance based on an inkjet method and a low relative dielectric constant. In addition, an electronic device encapsulation film using the composition for electronic device encapsulation and a method for forming the electronic device encapsulation film are provided.
[0012] In order to solve the above-mentioned problems, the inventors have studied the causes of the above-mentioned problems, and in the process found that by containing (meth)acrylate as a photopolymerizable monomer, and the dipole moment (μ), SP value (hydrogen bonding term δH) and molecular volume (V) of the photopolymerizable monomer satisfying specific conditions, it is possible to form an electronic device packaging film with excellent ejection stability, luminescent properties and crack resistance based on the inkjet method, and low dielectric. The present invention is thus completed.
[0013] That is, the above-mentioned problems of the present invention are solved by the following means.
[0014] 1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator,
[0015] contains (meth)acrylate as the photopolymerizable monomer,
[0016] Based on the dipole moment μ[Debye], molecular volume V[cm 3 ·mol -1 ] and hydrogen bonding term δH[MPa 1 / 2 ] and the following S1 calculated is 0.10×10 -2 ~1.10×10 -2 [Debye / (cm 3 ·mol -1 )], or the following S2 is within 0.50×10 -2 ~1.50×10 -2 [MPa 1 / 2 / (cm 3 ·mol -1 )].
[0017] S1=(m1×μ1+m2×μ2+···) / (m1×V1+m2×V2+···)
[0018] S2=(m1×δH1+m2×δH2+···) / (m1×V1+m2×V2+···)
[0019] (In the above formula, m is the molar ratio of the monomer, and the suffixes of m, μ, V and δH are the numbers of the monomers)
[0020] 2. The composition for encapsulating electronic devices according to item 1, wherein the S1 is 0.50×10 -2 ~0.80×10 -2 [Debye / (cm 3 ·mol -1 )], or the above S2 is within the range of 0.50×10 -2 ~1.00×10 -2 [MPa 1 / 2 / (cm 3 ·mol -1 )].
[0021] 3. The composition for encapsulating electronic devices according to item 1, wherein the hydrogen bonding term δH is in the range of 1.9 to 3.5 MPa. 1 / 2 within the range.
[0022] 4. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having:
[0023] a first encapsulation layer comprising silicon nitride, silicon oxide or silicon oxynitride, and
[0024] A second encapsulating layer using the composition for encapsulating an electronic device according to any one of items 1 to 3.
[0025] 5. The electronic device encapsulation film according to item 4, further comprising a third encapsulation layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulation layer.
[0026] 6. A method for forming an electronic device encapsulating film, which is a method for forming an electronic device encapsulating film using the composition for electronic device encapsulating any one of items 1 to 3, comprising:
[0027] forming a first encapsulation layer on the electronic device by a vapor phase method, and
[0028] A step of forming a second encapsulating layer by applying the electronic component encapsulating composition on the first encapsulating layer.
[0029] 7. The method for forming an electronic device encapsulation film according to item 6, further comprising the step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.
[0030] 8. The method for forming an electronic device encapsulation film according to item 6, wherein the second encapsulation layer is formed by an inkjet method.
[0031] According to the above method of the present invention, there is provided a composition for electronic device encapsulation that can form an electronic device encapsulation film having excellent ejection stability, luminescence characteristics and crack resistance based on an inkjet method and a low relative dielectric constant. In addition, there is provided an electronic device encapsulation film using the composition for electronic device encapsulation and a method for forming the electronic device encapsulation film.
[0032] The mechanism of expression and action of the effects of the present invention are not yet clear, but are presumed as follows.
[0033] In the present invention, based on the dipole moment μ[Debye] and molecular volume V[cm 3 ·mol -1 ] The above S1 calculated is the dipole moment per unit volume of the molecule, which is the value of the dipole moment normalized by the size of the molecule, based on the hydrogen bond term δH[MPa 1 / 2 ] and molecular volume V[cm 3 ·mol -1 ] The above-calculated S2 is δH per unit volume of the molecule, which is the value of the hydrogen bonding term component δH representing the SP value standardized by the size of the molecule.
[0034] (Discharge stability)
[0035] The inkjet head ejects minute droplets. Therefore, if a material with a large surface area per unit mass of liquid and high volatility, such as an organic solvent, is used, it will evaporate near the nozzle of the inkjet head, causing the viscosity to increase.
[0036] In contrast, in the present invention, (meth)acrylate is contained as a photopolymerizable monomer. Since it is an acrylic monomer, the volatility of the acrylic material is low, so the encapsulation composition of the present invention can be stably sprayed from the nozzle. Furthermore, by making the above-mentioned S1 or S2 within the above-mentioned specific range, the polarity becomes an appropriate range, the interaction between the monomers in the encapsulation composition becomes stronger, and the volatility becomes lower. From this point of view, it can also be inferred that the spraying stability is excellent.
[0037] (Luminescence characteristics)
[0038] Generally, when an electronic device (eg, an organic EL element) is stored at a high temperature (eg, 85° C.), components of the encapsulation layer diffuse, and if the diffusion is fast, the components may reach the encapsulated organic EL element.
[0039] However, even if the components of the encapsulation layer reach the organic EL element, there is no problem as long as they do not affect the organic layer and electrodes of the organic EL element. Therefore, it is speculated that whether it is easy to diffuse and whether it affects the organic layer and electrodes is related to the molecular size and polarity of the components of the encapsulation layer (i.e., the encapsulation composition).
[0040] Therefore, it is estimated that when the above S1 or the above S2 is within the above specific range, an electronic device with excellent light-emitting characteristics can be obtained.
[0041] (Crack resistance (appearance when bent and stored in a low-temperature environment))
[0042] In a low-temperature environment, the encapsulation layer formed by the encapsulation composition undergoes thermal shrinkage. In addition, when stored in a low-temperature environment in a bent state, further thermal shrinkage occurs, thereby applying stress to the encapsulation layer, causing peeling or cracking. Here, it is believed that thermal shrinkage is affected by the structure in which the molecules in the encapsulation layer are filled or how the molecules interact with each other.
[0043] Therefore, it is speculated that by keeping the above S1 or the above S2 within the above specific range, the molecular size and polarity of the components of the encapsulation layer (i.e., the encapsulation composition) become within the appropriate range, reducing the influence of thermal shrinkage, and improving the appearance (crack resistance) when bent and stored in a low-temperature environment.
[0044] (Low dielectric)
[0045] The organic EL element is preferably not easily polarized when an electric field is applied, and whether or not it is polarized is considered to depend on the directionality and mobility of the molecules of the components of the encapsulating film after the encapsulating composition is cured. Therefore, it is preferred that the molecules are less likely to move.
[0046] Therefore, it is estimated that when the above S1 or the above S2 is within the above specific range, the ratio of the molecular size and polarity of the components of the encapsulating composition is within an appropriate range, the interaction between molecules is maximized, the molecules become less mobile, and low dielectric constant is achieved (relative dielectric constant becomes low). DETAILED DESCRIPTION
[0047] The composition for encapsulating electronic devices of the present invention is a composition for encapsulating electronic devices containing a photopolymerizable monomer and a photopolymerization initiator, wherein the composition contains a (meth)acrylate as the photopolymerizable monomer, and the photopolymerizable monomer has a dipole moment μ[Debye], a molecular volume V[cm 3 ·mol -1 ] and hydrogen bonding term δH[MPa 1 / 2 ] and the following S1 calculated is 0.10×10 -2 ~1.10×10 -2 [Debye / (cm 3 ·mol-1 )], or the following S2 is within 0.50×10 -2 ~1.50×10 -2 [MPa 1 / 2 / (cm 3 ·mol -1 )].
[0048] S1=(m1×μ1+m2×μ2+···) / (m1×V1+m2×V2+···)
[0049] S2=(m1×δH1+m2×δH2+···) / (m1×V1+m2×V2+···)
[0050] (In the above formula, m is the molar ratio of the monomer, and the suffixes of m, μ, V and δH are the numbers of the monomers)
[0051] This feature is a technical feature shared or corresponding to the following embodiments.
[0052] As an embodiment of the present invention, it is preferred that S1 is within 0.50×10 -2 ~0.80×10 -2 [Debye / (cm 3 ·mol -1 )], or the above S2 is within the range of 0.50×10 -2 ~1.00×10 -2 [MPa 1 / 2 / (cm 3 ·mol -1 )].
[0053] In addition, from the perspective of crack resistance, it is preferred that the hydrogen bonding term δH is between 1.9 and 3.5 MPa. 1 / 2 within the range.
[0054] The electronic device encapsulating film of the present invention is an electronic device encapsulating film for encapsulating an electronic device, and comprises a first encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride, and a second encapsulating layer using the above-mentioned composition for encapsulating an electronic device.
[0055] This makes it possible to produce an electronic device packaging film that is excellent in ejection stability, light-emitting characteristics, and crack resistance by an inkjet method and has a low relative dielectric constant.
[0056] From the viewpoint of excellent encapsulation performance, it is preferred that a third encapsulation layer containing silicon nitride, silicon oxide or silicon oxynitride is provided on the second encapsulation layer.
[0057] The method for forming an electronic device packaging film of the present invention is a method for forming an electronic device packaging film using the above-mentioned electronic device packaging composition, comprising: a step of forming a first packaging layer on an electronic device by a vapor phase method, and a step of forming a second packaging layer by coating the above-mentioned electronic device packaging composition on the above-mentioned first packaging layer.
[0058] This makes it possible to produce an electronic device packaging film that is excellent in ejection stability, light-emitting characteristics, and crack resistance by an inkjet method and has a low relative dielectric constant.
[0059] From the viewpoint of excellent encapsulation performance, it is preferable to include a step of forming a third encapsulation layer on the second encapsulation layer by a vapor phase method.
[0060] In addition, from the viewpoint of being able to form the layer with high precision, it is preferable to form the second encapsulating layer by an inkjet method.
[0061] Hereinafter, the present invention and its constituent elements and forms and modes for carrying out the present invention will be described. It should be noted that in the present application, "to" is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0062] [Overview of the inkjet electronic device encapsulation composition of the present invention]
[0063] The composition for encapsulating electronic components for inkjet of the present invention (hereinafter, also referred to as "encapsulating composition") is a composition for encapsulating electronic components containing a photopolymerizable monomer and a photopolymerization initiator, wherein the composition contains a (meth)acrylate as the photopolymerizable monomer, and the photopolymerizable monomer has a dipole moment μ[Debye], a molecular volume V[cm 3 ·mol -1 ] and hydrogen bonding term δH[MPa 1 / 2 ] and the following S1 calculated is 0.10×10 -2 ~1.10×10 -2 [Debye / (cm 3 ·mol -1 )], or the following S2 is within 0.50×10 -2 ~1.50×10 -2 [MPa 1 / 2 / (cm 3 ·mol -1 )].
[0064] S1=(m1×μ1+m2×μ2+···) / (m1×V1+m2×V2+···)
[0065] S2=(m1×δH1+m2×δH2+···) / (m1×V1+m2×V2+···)
[0066] (In the above formula, m is the molar ratio of the monomer, and the suffixes of m, μ, V and δH are the numbers of the monomers)
[0067] <Dipole moment(μ)>
[0068] The dipole moment (μ) can be calculated using chemical structure information computer software. Examples of the calculation software include quantum chemical calculation programs "Gaussian series" manufactured by HULINKS.
[0069] The dipole moment in the present invention is obtained from the chemical structure information using Gaussian software manufactured by HULINKS Co., Ltd. The semi-empirical method PM6 is used in the calculation.
[0070] The dipole moment (μ) of each photopolymerizable monomer is -2 ~1.10×10 -2 [Debye / (cm 3 ·mol -1 )], but is preferably in the range of 0.5 to 1.7 Debye from the viewpoint of compatibility of the photopolymerizable monomers and solubility of the photopolymerization initiator.
[0071] <Molecular volume (V)>
[0072] The above molecular volume (V) represents the molecular volume per unit mole. The molar volume can be calculated from chemical structure information by using computer software.
[0073] The molecular volume (V) in the present invention is obtained from the information of chemical structure using the software Hansen Solubility Parameters in Practice (HSPiP) to obtain the molecular volume (V) of each monomer (unit: cm 3 ·mol -1 ).
[0074] The molecular volume (V) of each photopolymerizable monomer is as long as S1 is within 0.10×10 -2 ~1.10×10 -2 [Debye / (cm 3 ·mol -1 )] or S2 at 0.50×10 -2 ~1.50×10 -2 [MPa 1 / 2 / (cm 3 ·mol-1 )] is not particularly limited, but is preferably 150 to 600 (cm 3 ·mol -1 ) within the range of .
[0075] <Hydrogen bond term (δH)>
[0076] The hydrogen bonding term (δH) represents the hydrogen bonding term component of the Hansen solubility parameter. The Hansen solubility parameter is obtained by setting the Hildebrand solubility parameter to be a dispersion force, a dipole force, and a hydrogen bonding force, and dividing it into three components: a dispersion term component δD, a polar term component δP, and a hydrogen bonding term component δH. δH can be calculated from chemical structure information using computer software.
[0077] The hydrogen bonding term (δH) in the present invention is obtained from the chemical structure information using the software Hansen Solubility Parameters in Practice (HSPiP) (unit: MPa) of each monomer. 1 / 2 ).
[0078] The hydrogen bonding term δH of each photopolymerizable monomer is preferably between 1.9 and 3.5 MPa. 1 / 2 within the range.
[0079] The molar ratio m of the above monomers refers to the molar ratio of each monomer when the total number of moles of all monomers is taken as 1.
[0080] In order to make S1 calculated from the dipole moment (μ) and molecular volume (V) of the photopolymerizable monomer within 0.10×10 -2 ~1.10×10 -2 [Debye / (cm 3 ·mol -1 )], for example, a photopolymerizable monomer having a structure with a low dipole moment and a structure with a large molecular volume can be used.
[0081] Examples of the structure with a low dipole moment include a structure with a small number of hydroxyl groups, a structure with a small number of heteroatoms, a structure with a small number of ester groups, a structure of alicyclic hydrocarbons, and a highly symmetrical structure in which dipole moments cancel each other out.
[0082] Examples of the structure with a large molecular volume include an alicyclic structure, a structure with a large molecular weight, and a structure having an alkylene group with a carbon chain of 8 or more.
[0083] In order to make S2 calculated by using the molecular volume (V) and hydrogen bonding term (δH) of the photopolymerizable monomer within 0.50×10 -2 ~1.50×10 -2 [MPa1 / 2 / (cm 3 ·mol -1 )], for example, a photopolymerizable monomer having a structure with low hydrogen bonding ability and a large molecular volume can be used.
[0084] Examples of the structure having low hydrogen bonding properties include a structure having a small number of hydroxyl groups, a structure having a small number of heteroatoms, a structure having a small number of ester groups, a methacrylate structure, an alicyclic hydrocarbon structure, and a structure containing fluorine.
[0085] Examples of the structure with a large molecular volume include an alicyclic structure, a structure with a large molecular weight, and a structure having an alkylene group with a carbon chain of 8 or more.
[0086] [Composition of the composition for encapsulating electronic devices]
[0087] The composition for encapsulating electronic components of the present invention contains a photopolymerizable monomer and a photopolymerization initiator.
[0088] As the photopolymerizable monomer, a (meth)acrylate is contained.
[0089] In the present specification, "(meth)acrylate" means at least one of acrylate and methacrylate.
[0090] In addition, the "electronic device" in the present invention refers to an element that generates, amplifies, converts or controls electrical signals by using the kinetic energy and potential energy of electrons. Examples include active elements such as light emitting diode elements, organic electroluminescent elements, photoelectric conversion elements and transistors. In addition, in the present invention, passive elements such as resistors and capacitors that passively work by "impeding" or "accumulating" other actions are also included in the electronic device.
[0091] Therefore, the encapsulating composition of the present invention is used to form an encapsulating film for encapsulating the above-mentioned electronic device.
[0092] <Photopolymerizable monomer>
[0093] The "photopolymerizable monomer" refers to a photopolymerizable monomer (also referred to as a "photocurable monomer") that can undergo a polymerization (curing) reaction by absorbing light by itself or by a photopolymerization initiator to generate active ions or radicals.
[0094] As the photopolymerizable monomer, a non-silicon monomer that does not contain silicon (Si) can be used, for example, a monomer consisting of only elements selected from C, H, O, N or S, but not limited thereto. The photopolymerizable monomer can be synthesized by a common synthesis method and used, or it can be purchased as a commercially available product and used.
[0095] Examples of the photopolymerizable monomer include the photopolymerizable monomer (A) having no aromatic hydrocarbon group and the photopolymerizable monomer (B) having an aromatic hydrocarbon group described below. The photopolymerizable monomer (A) and (B) may be appropriately selected so that S1 or S2 satisfies the above range.
[0096] <Photopolymerizable monomer (A) not having an aromatic hydrocarbon group>
[0097] The above-mentioned photopolymerizable monomer (A) not having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (A)") does not contain an aromatic hydrocarbon group, and may contain a monomer having 1 to 20, specifically 1 to 6, one or more selected from vinyl, acrylic and methacrylic groups as photocurable functional groups (photopolymerizable functional groups), for example, it may contain 1 to 3, 1 to 2, 1 or 2.
[0098] In the present invention, the weight average molecular weight of the photopolymerizable monomer (A) can be in the range of 100 to 500 g / mol, in the range of 130 to 400 g / mol, or in the range of 200 to 300 g / mol. By being within the weight average molecular weight range of the monomer, a more favorable effect can be exhibited in the process.
[0099] The photopolymerizable monomer (A) may include a monofunctional monomer or a polyfunctional monomer having a photocurable functional group, or a mixture thereof.
[0100] Specifically, the above-mentioned photopolymerizable monomer (A) can be a (meth)acrylate monomer, or it can be an unsaturated carboxylic acid ester having an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, a hydroxyl group and an alkyl group having 1 to 20 carbon atoms; an unsaturated carboxylic acid ester having an aminoalkyl group having 1 to 20 carbon atoms; a vinyl ester of a saturated or unsaturated carboxylic acid having 1 to 20 carbon atoms; a vinyl cyanide compound; an unsaturated amide compound; a monofunctional or polyfunctional (meth)acrylate of a monohydric alcohol or a polyhydric alcohol, etc.
[0101] The above-mentioned "polyol" is an alcohol having two or more hydroxyl groups, and can refer to an alcohol having 2 to 20, preferably 2 to 10, more preferably 2 to 6 hydroxyl groups.
[0102] In one example, the (meth)acrylate monomer having no aromatic hydrocarbon group in the photopolymerizable monomer (A) may be a mono(meth)acrylate, a di(meth)acrylate, a tri(meth)acrylate, a tetra(meth)acrylate, or the like having a substituted or unsubstituted C1-C20 (carbon number 1-20) alkyl group, a substituted or unsubstituted C1-C20 alkylsilyl group, a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C1-C20 alkylene group, an amine group, an oxirane group, or the like.
[0103] Specifically, the (meth)acrylate monomers not having an aromatic hydrocarbon group may include: unsaturated carboxylic acid esters including (meth)acrylate such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, and cyclohexyl (meth)acrylate; unsaturated carboxylic acid aminoalkyl esters such as 2-aminoethyl (meth)acrylate and 2-dimethylaminoethyl (meth)acrylate; saturated or unsaturated carboxylic acid vinyl esters such as vinyl acetate; vinyl cyanide compounds such as (meth)acrylonitrile; unsaturated amide compounds such as (meth)acrylamide; ethylene glycol di(meth)acrylate; di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate or a mixture thereof, but is not limited thereto.
[0104] In one example of the present invention, the photopolymerizable monomer (A) is a non-aromatic system containing no aromatic group, and may include at least any one of a mono(meth)acrylate having an alkyl group having 1 to 20 carbon atoms, a mono(meth)acrylate having an amine group, a di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a di(meth)acrylate having an ethylene oxide group, a tri(meth)acrylate having an ethylene oxide group, and a mono(meth)acrylate and a di(meth)acrylate having a cyclic carbonized alkyl group.
[0105] The mono(meth)acrylate having a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms may specifically be decyl(meth)acrylate, undecyl(meth)acrylate, lauryl(meth)acrylate, tridecyl(meth)acrylate, tetradecyl(meth)acrylate, pentadecyl(meth)acrylate, hexadecyl(meth)acrylate, heptadecyl(meth)acrylate, octadecyl(meth)acrylate, nonadecyl(meth)acrylate, eicosyl(meth)acrylate or a mixture thereof, but is not limited thereto.
[0106] The mono(meth)acrylate having an amine group may be 2-aminoethyl(meth)acrylate, 2-dimethylaminoethyl(meth)acrylate, or a mixture thereof, but is not limited thereto.
[0107] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, a di(meth)acrylate having an alkylene group having 1 to 20 carbon atoms, or a non-silicon-based di(meth)acrylate containing a substituted or unsubstituted long-chain alkylene group.
[0108] The di(meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms may be, for example, octanediol di(meth)acrylate, nonanediol di(meth)acrylate, decanediol di(meth)acrylate, undecanediol di(meth)acrylate, dodecanediol di(meth)acrylate or a mixture thereof, but is not limited thereto.
[0109] When the (meth)acrylate having a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms is contained, the photocuring rate of the encapsulating composition of the present invention is further improved, and the viscosity can be reduced.
[0110] The di(meth)acrylate or tri(meth)acrylate having an ethylene oxide group is specifically ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, or a mixture thereof, but is not limited thereto.
[0111] The mono(meth)acrylate and di(meth)acrylate having a cyclic carbonized alkyl group may specifically be isobornyl(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dicyclopentanyl(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, and dicyclopentenyl(meth)acrylate, but are not limited thereto.
[0112] The photopolymerizable monomer (A) is preferably contained in an amount of 55 to 95% by mass, more preferably 60 to 90% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). Within the above range, the viscosity of the encapsulating composition of the present invention is suitable for forming an encapsulating film for electronic devices.
[0113] <Photopolymerizable monomer (B) having an aromatic hydrocarbon group>
[0114] The above-mentioned photopolymerizable monomer (B) having an aromatic hydrocarbon group (hereinafter also referred to as "photopolymerizable monomer (B)") contains two or more phenyl groups and hetero atoms having a structure represented by the following general formula (1), and the above-mentioned photopolymerizable monomer (B) contains at least mono(meth)acrylate or di(meth)acrylate.
[0115] General formula (1)
[0116]
[0117] [In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups. 1 and Z 2 Each independently has a structure represented by the following general formula (2). a and b are each an integer from 0 to 2, and a+b is an integer from 1 to 4]
[0118] General formula (2)
[0119]
[0120] [In the above general formula (2), * is a linking part to the carbon of P. X represents a single bond, O or S. Y represents a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms. R 1 represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. c is an integer of 0 or 1]
[0121] In the above general formula (1), P represents a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.
[0122] The above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the hydrocarbon group containing heteroatoms containing two or more substituted or unsubstituted phenyl groups means that the two or more substituted or unsubstituted phenyl groups are not condensed, but are hydrocarbon groups connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 5 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group.
[0123] For example, the above-mentioned hydrocarbon group containing two or more phenyl groups or the heteroatom-containing hydrocarbon group containing two or more phenyl groups may include substituted or unsubstituted biphenyl, substituted or unsubstituted triphenylmethyl, substituted or unsubstituted terphenyl, substituted or unsubstituted biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted quaterphenylene, substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl, substituted or unsubstituted 2,2-diphenylpropane, substituted or unsubstituted diphenylmethane, substituted or unsubstituted cumylphenyl, substituted or unsubstituted bisphenol F group, substituted or unsubstituted bisphenol A group, substituted or unsubstituted biphenyloxy, substituted or unsubstituted terphenyloxy, substituted or unsubstituted quaterphenyloxy, substituted or unsubstituted pentphenyloxy and their structural isomers, but are not limited thereto.
[0124] The monomer having two or more substituted or unsubstituted phenyl groups may be a mono(meth)acrylate, a di(meth)acrylate or a mixture thereof, and examples thereof include 4-(meth)acryloyloxy-2-hydroxybenzophenone, ethyl-3,3-diphenyl(meth)acrylate, benzoyloxyphenyl(meth)acrylate, bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, 4-cumylphenoxyethyl acrylate, ethoxylated bisphenylfluorene diacrylate, 2-phenylphenoxyethyl(meth)acrylate, 2,2'-phenylphenoxyethyl di(meth)acrylate, 2-phenylphenoxypropyl(meth)acrylate, 2,2'-phenylphenoxypropyldi(meth)acrylate, 2-phenylphenoxybutyl(meth)acrylate, 2,2'-phenylphenoxybutyldi(meth)acrylate, 2 2-(3-phenylphenyl)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 2-phenyl-2-(phenylthio)ethyl (meth)acrylate, 2-(triphenylmethoxy)ethyl (meth)acrylate, 4-(triphenylmethoxy)butyl (meth)acrylate, 3-(biphenyl-2-yloxy)butyl (meth)acrylate, 2-(biphenyl-2-yloxy)butyl (meth)acrylate, 4-(biphenyl-2-yloxy)propyl (meth)acrylate, 3-(biphenyl-2-yloxy)propyl acrylate, 2-(biphenyl-2-yloxy)propyl (meth)acrylate, 4-(biphenyl-2-yloxy)ethyl (meth)acrylate, 3-(biphenyl-2-yloxy)ethyl (meth)acrylate, 2-(4-benzylphenyl)ethyl (meth)acrylate, 4,4'-bis(acryloyloxymethyl)biphenyl, 2,2'-bis(2-acryloyloxyethoxy)biphenyl, structural isomers thereof or mixtures thereof, but not limited thereto.
[0125] In addition, the (meth)acrylate mentioned in the present invention is just an example and is not limited thereto.
[0126] Furthermore, the present invention includes all acrylates in a structural isomer relationship. For example, even if only 2,2'-phenylphenoxyethyl di(meth)acrylate is mentioned as an example of the present invention, the present invention also includes all 3,2'-phenylphenoxyethyl di(meth)acrylate, 3,3'-phenylphenoxyethyl di(meth)acrylate, etc. corresponding to the structural isomer.
[0127] In one example of the present invention, the monomer having two or more phenyl groups may be a mono(meth)acrylate represented by the following general formula (4).
[0128] General formula (4)
[0129]
[0130] In the above general formula (4), R 2 is hydrogen or methyl, R 3 is a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, R 4 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.
[0131] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the hydrocarbon group containing heteroatoms containing two or more substituted or unsubstituted phenyl groups means that the two or more substituted or unsubstituted phenyl groups are not condensed, but are hydrocarbon groups connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 3 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group.
[0132] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups may include substituted or unsubstituted biphenyl, substituted or unsubstituted triphenylmethyl, substituted or unsubstituted terphenyl, substituted or unsubstituted biphenylene, substituted or unsubstituted terphenylene, substituted or unsubstituted quaterphenylene, substituted or unsubstituted 2-phenyl-2-(phenylthio)ethyl, substituted or unsubstituted 2,2-diphenylpropane, substituted or unsubstituted diphenylmethane, substituted or unsubstituted cumylphenyl, substituted or unsubstituted bisphenol F group, substituted or unsubstituted bisphenol A group, substituted or unsubstituted biphenyloxy, substituted or unsubstituted terphenyloxy, substituted or unsubstituted quaterphenyloxy, substituted or unsubstituted pentphenyloxy, etc., but are not limited thereto.
[0133] In one example of the present invention, the monomer having two or more phenyl groups may be a di(meth)acrylate represented by the following general formula (5).
[0134] General formula (5)
[0135]
[0136] In the above general formula (5), R 5 , R 9 are each independently hydrogen or methyl, R 6 , R 8 are each independently a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, or a substituted or unsubstituted alkoxy group having 1 to 20 carbon atoms, 7 It is a hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or a heteroatom-containing hydrocarbon group containing two or more substituted or unsubstituted phenyl groups.
[0137] For example, the above-mentioned hydrocarbon group containing two or more substituted or unsubstituted phenyl groups, or the hydrocarbon group containing heteroatoms containing two or more substituted or unsubstituted phenyl groups means that the two or more substituted or unsubstituted phenyl groups are not condensed, but are hydrocarbon groups connected by a single bond, an oxygen atom, a sulfur atom, a substituted or unsubstituted alkyl group having 1 to 4 carbon atoms, an alkylene group having 3 to 6 carbon atoms substituted or unsubstituted by a heteroatom, a vinylene group, an ethynylene group or a carbonyl group.
[0138] For example, the hydrocarbon group may include substituted or unsubstituted biphenylene, substituted or unsubstituted triphenylmethylene, substituted or unsubstituted terphenylene, substituted or unsubstituted quaterphenylene, 2-phenyl-2-(phenylthio)ethylene, 2,2-diphenylpropylene, diphenylmethylene, etc., but is not limited thereto.
[0139] In the above general formula (1), a and b are integers of 0 to 2 respectively, and a+b is an integer of 1 to 4. In one example, a+b is an integer of 1 or 2.
[0140] The weight average molecular weight of the monomer having two or more substituted or unsubstituted phenyl groups is preferably in the range of 100 to 1000 g / mol, more preferably in the range of 130 to 700 g / mol, and particularly preferably in the range of 150 to 600 g / mol.
[0141] When the content is within the above range, a packaging film having a higher transmittance can be provided.
[0142] The photopolymerizable monomer (B) having an aromatic hydrocarbon group is preferably contained in an amount of 5 to 45% by mass, more preferably 10 to 40% by mass, relative to the total mass of the photopolymerizable monomers (photopolymerizable monomer (A) and photopolymerizable monomer (B)). Within the above range, the viscosity is suitable for forming a packaging film.
[0143] Specific examples of the photopolymerizable monomers (A) and (B) include the monomers listed in the examples described below in addition to the above monomers. Preferred combinations of the photopolymerizable monomers in the present invention are described in the examples described below.
[0144] <Photopolymerization initiator>
[0145] The photopolymerization initiator is not particularly limited as long as it is a common photopolymerization initiator capable of performing a photopolymerization reaction.
[0146] As the photopolymerization initiator, for example, a triazine-based, acetophenone-based, benzophenone-based, thioxanthone-based, benzoin-based, phosphorus-based, oxime-based, or a mixture thereof may be included.
[0147] The triazine initiator can be 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, s-triazine, 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl(piperonyl)-6-triazine, 2,4-(trichloromethyl(4'-methoxyphenylvinyl)-6-triazine or a mixture thereof.
[0148] The acetophenone-based initiator may be 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, p-tert-butyltrichloroacetophenone, p-tert-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, and mixtures thereof.
[0149] The benzophenone-based initiator may be benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-dichlorobenzophenone, 3,3'-dimethyl-2-methoxybenzophenone or a mixture thereof.
[0150] The thioxanthone-based initiator may be thioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chlorothioxanthone or a mixture thereof.
[0151] The benzoin-based initiator may be benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzil dimethyl ketal or a mixture thereof.
[0152] The phosphorus-based initiator may be bisbenzoylphenylphosphine oxide, benzoyldiphenylphosphine oxide or a mixture thereof.
[0153] The oxime system may be 2-(o-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione and 1-(o-acetoxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone or a mixture thereof.
[0154] The photopolymerization initiator is preferably contained in the encapsulation composition of the present invention in an amount of about 0.1 to 20 parts by mass relative to 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. Within the above range, photopolymerization can be fully carried out during exposure, and a decrease in transmittance due to residual unreacted initiator after photopolymerization can be prevented.
[0155] Specifically, the photopolymerization initiator is preferably contained in an amount within a range of 0.5 to 10 parts by mass, more specifically, within a range of 1 to 5 parts by mass.
[0156] In addition, the photopolymerization initiator is preferably contained in the encapsulating composition of the present invention in an amount of 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, based on the solid content. Within the above range, photopolymerization can be sufficiently carried out and a decrease in transmittance due to residual unreacted initiator can be prevented.
[0157] In addition, carbazole-based, diketone-based, sulfonium-based, iodine-based A photoacid generator or photopolymerization initiator of a type, a diazo type, a biimidazole type, etc. can be used instead of the above-mentioned photopolymerization initiator.
[0158] <Other additives>
[0159] The encapsulation composition of the present invention may further contain other components including antioxidants, heat stabilizers, photosensitizers, dispersants, thermal crosslinking agents and surfactants within the scope of obtaining the effects of the present invention. These components may be contained in the encapsulation composition of the present invention alone or in combination of two or more.
[0160] The above antioxidant can improve the thermal stability of the encapsulation layer. The antioxidant may include one or more selected from phenol, quinone, amine and phosphite, but is not limited thereto. For example, as an antioxidant, tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, tris(2,4-di-tert-butylphenyl)phosphite, etc. may be cited.
[0161] The antioxidant is preferably contained in the encapsulating composition in an amount of 0.01 to 3 parts by mass, more preferably 0.01 to 1 part by mass, based on 100 parts by mass of the total of the photopolymerizable monomer and the photopolymerization initiator. Within the above range, excellent thermal stability can be exhibited.
[0162] The heat stabilizer is contained in the encapsulating composition to suppress a change in viscosity of the encapsulating composition at room temperature, and any common heat stabilizer can be used without limitation.
[0163] For example, as the heat stabilizer, a sterically hindered phenolic heat stabilizer can be used, and specifically, it can include poly(dicyclopentadiene-co-p-cresol), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylene-bis(4-methyl-6-tert-butylphenol), 6,6'-di-tert-butyl-2,2'-thiodi-p-cresol, tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, triethylene glycol-bis(3-tert-butyl-4-hydroxy-5-methylphenyl), 4,4'-thiobis(6-tert-butyl-m-cresol), 3,3' -bis(3,5-di-tert-butyl-4-hydroxyphenyl)-N,N'-hexamethylene-bispropionamide, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), stearyl-3,5-di-tert-butyl-4-hydroxyphenylpropionate, pentaerythritol tetrakis-1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butyl-benzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(2-hydroxyethyl)isocyanurate-tris(3,5-di-tert-butylhydroxyphenylpropionate), but not limited thereto.
[0164] The thermal stabilizer is contained in the encapsulating composition in an amount of 2000 ppm or less, preferably in a range of 0.01 to 2000 ppm, and more preferably in a range of 100 to 1000 ppm, based on the solid content relative to the total of the photopolymerizable monomer and the photopolymerization initiator. By being within the above range, the thermal stabilizer can further improve the storage stability and processability of the encapsulating composition in a liquid state.
[0165] The photosensitizer is a compound that has a function of transferring absorbed light energy to a photopolymerization initiator, and thus can impart the original photopolymerization initiator function even if the photopolymerization initiator used does not have absorption corresponding to light from a light source.
[0166] Examples of the photosensitizer include anthracene derivatives such as 9,10-dibutoxyanthracene; benzoin derivatives such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether;
[0167] Benzophenone derivatives such as benzoylbenzoic acid methyl ester, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propyleneoxy)ethyl]benzyl ammonium bromide, and (4-benzoylbenzyl)trimethylammonium chloride;
[0168] Thioxanthone derivatives such as 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one meso chloride; and other compounds. Among them, anthracene derivatives, benzoin derivatives, benzophenone derivatives, anthraquinone derivatives, and thioxanthone derivatives are preferably used.
[0169] <Ultraviolet curing>
[0170] As the ultraviolet rays irradiated to cure the encapsulating composition of the present invention, a known method can be used, and there is no particular limitation as long as the curing is carried out by irradiating ultraviolet rays in the range of 200 to 400 nm. Ideally, from the viewpoint of preventing degradation of electronic devices, a 395 nm LED is preferably used.
[0171] The environment for irradiating ultraviolet rays can be a known method as long as the encapsulation composition is cured, and there is no particular limitation as long as it is cured by irradiating ultraviolet rays. Ideally, from the viewpoint of preventing degradation of electronic devices and preventing the influence of curing hindrance caused by oxygen, it is preferably irradiated in an inert gas environment. It is particularly preferred to irradiate under a nitrogen or argon atmosphere.
[0172] <Physical Properties>
[0173] The viscosity of the encapsulating composition of the present invention is preferably in the range of 3 to 30 mPa·s from the viewpoint of further improving the dischargeability from an inkjet head. The surface tension is preferably 15 mN / m or more and less than 45 mN / m from the viewpoint of further improving the dischargeability from an inkjet head.
[0174] The viscosity of the encapsulating composition of the present invention can be determined, for example, by measuring the temperature change of the dynamic viscoelasticity of the encapsulating composition using various rheometers.
[0175] In the present invention, these viscosities are values obtained by the following method. The encapsulation composition of the present invention is placed in a stress-controlled rheometer Physica MCR300 (diameter of vertebral plate: 75 mm, cone angle: 1.0°), manufactured by Anton Paar. Next, the encapsulation composition is heated to 100°C, and the encapsulation composition is cooled to 20°C under the conditions of a cooling rate of 0.1°C / s, a strain of 5%, and an angular frequency of 10 radian / s to obtain a temperature change curve of dynamic viscoelasticity.
[0176] The encapsulating composition of the present invention may contain pigment particles. For the pigment particles, from the viewpoint of further improving the ejection property from the inkjet head, when the encapsulating composition of the present invention contains a pigment, the average particle size of the pigment particles is preferably in the range of 0.08 to 0.5 μm, and the maximum particle size is preferably in the range of 0.3 to 10 μm.
[0177] The average particle size of the pigment particles in the present invention refers to the value obtained by the dynamic light scattering method using Zetasizer Nano ZSP, manufactured by Malvern. It should be noted that the concentration of the encapsulating composition containing the coloring material is high, and light does not pass through the measuring instrument, so the encapsulating composition is diluted 200 times before measurement. The measurement temperature is room temperature (25°C).
[0178] In addition, from the perspective of inkjet ejection properties and droplet stability during ink flight, the encapsulation composition of the present invention preferably has an Ohnesorg number (Oh) expressed by the following formula 1, which is a density ρ, a surface tension σ of the above-mentioned encapsulation composition, a viscosity μ of the above-mentioned encapsulation composition, and a nozzle diameter D0, in the range of 0.1 to 1.
[0179]
[0180] The encapsulation composition of the present invention is preferably prepared to provide a cured polymer having a Tg (glass transition temperature) of 80° C. or higher in the film after polymerization. From the viewpoint of the formation process of the electronic device, the driving temperature, and ensuring stability in the reliability test, the Tg of the film after polymerization is preferably 80° C. or higher.
[0181] [Method for forming an electronic device packaging film]
[0182] The method for forming an electronic device packaging film of the present invention is a method for forming a packaging film using the above-mentioned electronic device packaging composition of the present invention, comprising: a step of forming a first packaging layer on an electronic device by a vapor phase method, and a step of forming a second packaging layer by coating the above-mentioned electronic device packaging composition on the above-mentioned first packaging layer.
[0183] In addition, from the viewpoint of being able to further improve the sealing performance of the electronic device, it is preferable to include a step of forming a third sealing layer on the second sealing layer by a vapor phase method.
[0184] <First sealing layer forming step>
[0185] The first encapsulation layer forming step forms a first encapsulation layer on the electronic device by a vapor phase method.
[0186] As the gas phase method, there can be mentioned a sputtering method (for example, magnetron cathode sputtering, planar magnetron sputtering, two-pole AC planar magnetron sputtering, two-pole AC rotating magnetron sputtering, etc., including reactive sputtering), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), a thermal CVD method, a catalytic chemical vapor deposition method (Cat-CVD), a capacitively coupled plasma CVD method (CCP-CVD), a photo CVD method, a plasma CVD method (PECVD), an epitaxial growth method, a chemical vapor deposition method such as an atomic layer deposition method (ALD), etc. Among them, formation by an ALD method or a CVD method is preferred.
[0187] The first encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).
[0188] As a specific example of forming the first encapsulation layer, there is a method in which the pressure in the chamber is reduced in advance, and silane (SiH 4 ), ammonia (NH 3 ), and hydrogen (H 2 ) as raw material gases are heated and supplied into the chamber.
[0189] The thickness of the first encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.
[0190] <Second Encapsulation Layer Formation Step>
[0191] The second encapsulating layer forming step forms the second encapsulating layer by applying the encapsulating composition of the present invention onto the first encapsulating layer.
[0192] Specifically, the method may include a step of coating the encapsulating composition on the first encapsulating layer (coating step), and subjecting the obtained coating film to a modification treatment by irradiating it with vacuum ultraviolet rays in a nitrogen atmosphere.
[0193] (Coating process)
[0194] As a coating method for the encapsulation composition, any appropriate method can be adopted, for example, spin coating, roll coating, flow coating, inkjet, spray coating, printing, dip coating, cast film forming, rod coating, gravure printing, etc. Among them, the inkjet method is preferably used from the aspect of being able to perform fine patterning required when encapsulating electronic devices such as organic EL elements as needed.
[0195] As the inkjet method, a known method can be used.
[0196] The inkjet method is roughly divided into two types: the drop-on-demand method and the continuous method, both of which can be used. As the drop-on-demand method, there are electro-mechanical conversion methods (such as single-chamber type, dual-chamber type, curved type, piston type, shared module type, shared wall type, etc.), electro-thermal conversion methods (such as thermal inkjet type, BUBBLEJET (registered trademark) type, etc.), electrostatic attraction methods (such as electric field control type, slit jet type, etc.) and discharge methods (such as electric spark jet type, etc.). From the perspective of the cost and productivity of the inkjet head, it is preferred to use an inkjet head using an electro-mechanical conversion method or an electro-thermal conversion method. It should be noted that the method of dripping droplets (such as coating liquid) according to the inkjet method is sometimes called an "inkjet method".
[0197] The encapsulating composition is preferably applied under a nitrogen atmosphere.
[0198] (Reforming process)
[0199] The modification step may include a step of modifying the obtained coating film by irradiating it with vacuum ultraviolet rays in a nitrogen atmosphere after the coating step.
[0200] The modification treatment refers to a conversion reaction of polysilazane into silicon oxide or silicon oxynitride. The modification treatment is also performed in a nitrogen atmosphere and under reduced pressure in a glove box.
[0201] The modification treatment in the present invention can be selected from a known method based on the conversion reaction of polysilazane. In the present invention, it is preferred to use a conversion reaction of plasma, ozone, or ultraviolet light that can perform the conversion reaction at low temperature. Plasma and ozone can use a conventionally known method. In the present invention, it is preferred to form the second encapsulation layer of the present invention by providing the above-mentioned coating film and irradiating vacuum ultraviolet light (also referred to as VUV) with a wavelength of less than 200nm for modification treatment.
[0202] The thickness of the second encapsulating layer is preferably in the range of 0.5 to 20 μm, more preferably in the range of 3 to 10 μm.
[0203] The second encapsulating layer may be a layer whose entire layer is modified, and the thickness of the modified layer is preferably in the range of 1 to 50 nm, and more preferably in the range of 1 to 30 nm.
[0204] In the step of irradiating the coating film with vacuum ultraviolet rays for modification, the illuminance of the vacuum ultraviolet rays on the coating film surface is preferably 30 to 200 mW / cm 2 The range of 50 to 160 mW / cm 2 By making the illuminance of vacuum ultraviolet light 30mW / cm 2 Above, the reforming efficiency can be fully improved, at 200mW / cm 2 When the ratio is less than 0.1, the occurrence rate of damage to the coating film can be extremely suppressed, and damage to the substrate can also be reduced, which is preferred.
[0205] In the irradiation of vacuum ultraviolet rays, the irradiation energy of the vacuum ultraviolet rays on the coating film surface is preferably 1 to 10 J / cm 2 In the range of 3 to 7 J / cm2, from the viewpoint of maintaining the barrier property and moisture heat resistance for the dehumidification function, the 2 within the range.
[0206] It should be noted that as the light source of vacuum ultraviolet light, it is preferred to use a rare gas excimer lamp. Since vacuum ultraviolet light is due to the absorption based on oxygen, the efficiency in the vacuum ultraviolet light irradiation process is easily reduced, so the irradiation of vacuum ultraviolet light is preferably carried out under a low oxygen concentration as much as possible. That is, the oxygen concentration during vacuum ultraviolet light irradiation is preferably in the range of 10 to 10000ppm, more preferably in the range of 50 to 5000ppm, further preferably in the range of 80 to 4500ppm, and most preferably in the range of 100 to 1000ppm.
[0207] The modification treatment may also be combined with the heat treatment. By using the heat treatment at a temperature preferably in the range of 50 to 300° C., more preferably in the range of 60 to 150° C., and preferably for 1 second to 60 minutes, more preferably for 10 seconds to 10 minutes as the heating conditions, the dehydration condensation reaction during the modification can be promoted, and the modified body can be formed more effectively.
[0208] As the heating treatment, for example, there are methods of heating the coating film by heat conduction by bringing the substrate into contact with a heating body such as a heating block, a method of heating the atmosphere by using an external heater based on a resistance wire, etc., a method of using infrared light such as an IR heater, etc., without particular limitation. In addition, a method that can maintain the smoothness of the coating film containing the silicon compound can be appropriately selected.
[0209] <Third Encapsulation Layer Formation Step>
[0210] The third encapsulating layer forming step forms a third encapsulating layer on the second encapsulating layer by a vapor phase method.
[0211] As the gas phase method, similar to the gas phase method used in the first encapsulation layer forming step, there can be mentioned a sputtering method (for example, magnetron cathode sputtering, planar magnetron sputtering, two-pole AC planar magnetron sputtering, two-pole AC rotating magnetron sputtering, etc., including reactive sputtering), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), a thermal CVD method, a catalytic chemical vapor deposition method (Cat-CVD), a capacitively coupled plasma CVD method (CCP-CVD), a photo CVD method, a plasma CVD method (PE-CVD), an epitaxial growth method, a chemical vapor deposition method such as an atomic layer deposition method (ALD), etc. Among them, it is preferably formed by an ALD method or a CVD method.
[0212] The third encapsulation layer contains silicon nitride (SiNx), silicon nitride oxide (SiNOx), or silicon oxide (SiOx).
[0213] As a specific example of forming the third encapsulation layer, there is a method in which the pressure in the chamber is reduced in advance, and silane (SiH 4 ), ammonia (NH 3 ), and hydrogen (H 2 ) as raw material gases are heated and supplied into the chamber.
[0214] The thickness of the third encapsulation layer is, for example, preferably in the range of 10 to 1000 nm, more preferably in the range of 100 to 500 nm.
[0215] It should be noted that after the package film is formed as described above, a conductive film for a touch sensor may be further formed.
[0216] The conductive film may be composed of a metal compound film such as ITO (Indium Tin Oxide) or IZO (Indium Zinc Oxide), or a graphene film having excellent flexibility, a metal nanowire film (e.g., a film containing silver nanowires or copper nanowires), or a metal nanoparticle film (e.g., a film containing silver nanoparticles or copper nanoparticles). In addition, the conductive film may be composed of a laminated film of multiple metals such as Al film / Ti film / Al film.
[0217] [Electronic device packaging film]
[0218] The electronic device encapsulating film of the present invention is an electronic device encapsulating film for encapsulating an electronic device, and comprises a first encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride and a second encapsulating layer using the composition for encapsulating an electronic device of the present invention.
[0219] The electronic device encapsulating film of the present invention is formed by the above-mentioned method for forming an electronic device encapsulating film. That is, the second encapsulating layer is formed using the above-mentioned composition for encapsulating electronic devices of the present invention.
[0220] In addition, the electronic device encapsulating film of the present invention preferably further comprises a third encapsulating layer containing silicon nitride, silicon oxide or silicon oxynitride on the second encapsulating layer.
[0221] <1st packaging layer>
[0222] The first encapsulation layer is a layer formed on the electronic device by the above-mentioned vapor phase method, and specifically contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.), or silicon oxynitride.
[0223] <Second Encapsulation Layer>
[0224] The second encapsulating layer is provided adjacent to the first encapsulating layer, and is formed by applying the encapsulating composition onto the first encapsulating layer.
[0225] Therefore, the second encapsulating layer contains a polymer composed of the specific photopolymerizable monomer contained in the encapsulating composition.
[0226] As a method for detecting whether the second encapsulation layer contains the polymer, various conventionally known analytical methods can be used, such as chromatography, infrared spectroscopy, ultraviolet / visible spectroscopy, nuclear magnetic resonance analysis, X-ray diffraction and mass spectrometry, X-ray photoelectron spectroscopy, etc.
[0227] The content of the polymer in the second encapsulating layer is preferably in the range of 85 to 100% by mass, more preferably in the range of 90 to 95% by mass.
[0228] <Third Encapsulation Layer>
[0229] The third encapsulation layer is provided adjacent to the second encapsulation layer and is formed by the above-mentioned vapor phase method. Specifically, it contains silicon nitride, silicon oxide (silicon monoxide, silicon dioxide, etc.) or silicon oxynitride, similarly to the first encapsulation layer.
[0230] [Electronic devices]
[0231] In the method for forming an electronic device encapsulation film and the electronic device encapsulation film of the present invention, the encapsulated electronic device may be, for example, an organic EL element, an LED element, a liquid crystal display element (LCD), a thin film transistor, a touch panel, an electronic paper, a solar cell (PV), etc. From the viewpoint of more effectively obtaining the effect of the present invention, an organic EL element, a solar cell or an LED element is preferred, and an organic EL element is particularly preferred.
[0232] <Organic EL devices>
[0233] The organic EL element used as the electronic device of the present invention may be a bottom emission type organic EL element, that is, an organic EL element that extracts light from the transparent substrate side.
[0234] Specifically, the bottom emission type is constituted by laminating a transparent electrode as a cathode, a light-emitting functional layer, and a counter electrode as an anode in this order on a transparent substrate.
[0235] The organic EL element of the present invention may be a top emission type, that is, an organic EL element that extracts light from a transparent electrode side serving as a cathode opposite to a substrate.
[0236] Specifically, the top emission type has a structure in which a counter electrode as an anode is provided on the substrate side, and a light-emitting functional layer and a transparent electrode as a cathode are sequentially stacked on the surface thereof.
[0237] A typical example of the structure of an organic EL element is shown below.
[0238] (i) Anode / Hole injection and transport layer / Emitting layer / Electron injection and transport layer / Cathode
[0239] (ii) Anode / hole injection and transport layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode
[0240] (iii) Anode / hole injection and transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron injection and transport layer / cathode
[0241] (iv) Anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / cathode
[0242] (v) Anode / hole injection layer / hole transport layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode
[0243] (vi) anode / hole injection layer / hole transport layer / electron blocking layer / light-emitting layer / hole blocking layer / electron transport layer / electron injection layer / cathode
[0244] Furthermore, the organic EL element may have a non-luminescent intermediate layer. The intermediate layer may be a charge generating layer or may be composed of a multiphoton unit.
[0245] As an outline of the organic EL element applicable to the present invention, for example, Japanese Patent Application Laid-Open No. 2013-157634, Japanese Patent Application Laid-Open No. 2013-168552, Japanese Patent Application Laid-Open No. 2013-177361, Japanese Patent Application Laid-Open No. 2013-187211, Japanese Patent Application Laid-Open No. 2013-191644, Japanese Patent Application Laid-Open No. 2013-191804, Japanese Patent Application Laid-Open No. 2013-225678, Japanese Patent Application Laid-Open No. 2013-235994, Japanese Patent Application Laid-Open No. 2013- The configurations described in Japanese Patent Application Laid-Open No. 243234, Japanese Patent Application Laid-Open No. 2013-243236, Japanese Patent Application Laid-Open No. 2013-242366, Japanese Patent Application Laid-Open No. 2013-243371, Japanese Patent Application Laid-Open No. 2013-245179, Japanese Patent Application Laid-Open No. 2014-003249, Japanese Patent Application Laid-Open No. 2014-003299, Japanese Patent Application Laid-Open No. 2014-013910, Japanese Patent Application Laid-Open No. 2014-017493, Japanese Patent Application Laid-Open No. 2014-017494, etc.
[0246] <Base material>
[0247] As a substrate (hereinafter also referred to as a supporting substrate, base, substrate, support, etc.) that can be used for the above-mentioned organic EL element, specifically, glass or a resin film is preferably used. When flexibility is required, a resin film is preferably used.
[0248] In addition, it may be transparent or opaque. In the case of a so-called bottom emission type in which light is extracted from the substrate side, the substrate is preferably transparent.
[0249] Preferred resins include polyester resins, methacrylic resins, methacrylic acid-maleic acid copolymers, polystyrene resins, transparent fluorine resins, polyimides, fluorinated polyimide resins, polyamide resins, polyamide-imide resins, polyether-imide resins, cellulose acylate resins, polyurethane resins, polyether-ether-ketone resins, polycarbonate resins, alicyclic polyolefin resins, polyarylate resins, polyethersulfone resins, polysulfone resins, cycloolefin copolymers, fluorene ring-modified polycarbonate resins, alicyclic-modified polycarbonate resins, fluorene ring-modified polyester resins, acrylic compounds and other thermoplastic resins. The resins may be used alone or in combination of two or more.
[0250] The substrate is preferably made of a heat-resistant material. Specifically, a substrate having a linear expansion coefficient of 15 ppm / K to 100 ppm / K and a glass transition temperature (Tg) of 100°C to 300°C is used.
[0251] The substrate meets the necessary conditions for use in electronic components and as a laminated film for displays. That is, when the encapsulation film of the present invention is used in these applications, the substrate is sometimes exposed to a process above 150°C. In this case, if the linear expansion coefficient of the substrate exceeds 100ppm / K, the substrate size is unstable when flowing through the process at the temperature described above, and it is easy to produce the disadvantage of deterioration of barrier performance or the disadvantage of being unable to withstand the thermal process due to thermal expansion and contraction. When it is less than 15ppm / K, the film sometimes breaks like glass and the flexibility is deteriorated.
[0252] The Tg and linear expansion coefficient of the substrate can be adjusted by additives and the like.
[0253] More preferred specific examples of thermoplastic resins that can be used as the substrate include polyethylene terephthalate (PET: 70°C), polyethylene naphthalate (PEN: 120°C), polycarbonate (PC: 140°C), alicyclic polyolefins (e.g., ZEONOR (registered trademark) 1600 manufactured by Zeon Corporation: 160°C), polyarylate (PAr: 210°C), polyether sulfone (PES: 220°C), polysulfone (PSF: 190°C), cycloolefin copolymer (COC: described in Japanese Patent Application Laid-Open No. 2001-150584) and polyether sulfone (PES: 220°C). Compounds: 162°C), polyimides (e.g., Neopulim (registered trademark) manufactured by Mitsubishi Gas Chemical Co., Ltd.: 260°C), fluorene ring-modified polycarbonate (BCF-PC: compounds described in JP-A-2000-227603: 225°C), alicyclic modified polycarbonate (IP-PC: compounds described in JP-A-2000-227603: 205°C), acrylic compounds (compounds described in JP-A-2002-80616: 300°C or more), etc. (temperatures in parentheses represent Tg).
[0254] The electronic device of the present invention is an electronic device such as an organic EL element, so the substrate is preferably transparent. That is, the light transmittance is usually 80% or more, preferably 85% or more, and more preferably 90% or more. The light transmittance can be calculated by measuring the total light transmittance and the amount of scattered light using an integrating sphere light transmittance measuring device using the method described in JIS K7105:1981, and subtracting the diffuse transmittance from the total light transmittance.
[0255] In addition, the substrates mentioned above can be unstretched films or stretched films. The substrates can be manufactured by conventional methods known in the past. Regarding the manufacturing methods of these substrates, the matters described in paragraphs "0051" to "0055" of International Publication No. 2013 / 002026 can be appropriately adopted.
[0256] The surface of the substrate may be subjected to various known treatments for improving adhesion, such as corona discharge treatment, flame treatment, oxidation treatment or plasma treatment, or the above treatments may be combined as required. In addition, the substrate may be subjected to an easy-adhesion treatment.
[0257] The substrate may be a single layer or a laminated structure of two or more layers. When the substrate has a laminated structure of two or more layers, each substrate may be of the same type or of different types.
[0258] The thickness of the substrate of the present invention (the total thickness in the case of a laminated structure of two or more layers) is preferably 10 to 200 μm, more preferably 20 to 150 μm.
[0259] In the case of a film substrate, a film substrate with a gas barrier layer is preferred.
[0260] The gas barrier layer for the film substrate may be formed of an inorganic film, an organic film, or a mixed film of the two on the surface of the film substrate, and preferably has a water vapor permeability (25±0.5°C, relative humidity (90±2)% RH) of 0.01 g / m 2 The barrier film with a shelf life of 24 hours or less is more preferably an oxygen permeability of 1×10 -3 mL / m 2 ·24h·atm or less, water vapor transmission rate is 1×10 -3 g / m 2 ·High gas barrier film for less than 24 hours.
[0261] The gas barrier layer may be formed of any material as long as it has the function of suppressing the infiltration of substances such as moisture and oxygen that cause element degradation, and for example, silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, silicon oxycarbide, etc. can be used.
[0262] The gas barrier layer is not particularly limited. For example, in the case of an inorganic gas barrier layer such as silicon monoxide, silicon dioxide, silicon nitride, silicon oxynitride, silicon carbide, silicon oxycarbide, etc., it is preferred to form a layer of the inorganic material by using a sputtering method (for example, magnetron cathode sputtering, planar magnetron sputtering, diode AC planar magnetron sputtering, diode AC rotary magnetron sputtering, etc.), a vapor deposition method (for example, resistance heating vapor deposition, electron beam vapor deposition, ion beam vapor deposition, plasma assisted vapor deposition, etc.), a thermal CVD method, a catalytic chemical vapor deposition method (Cat-CVD), a capacitively coupled plasma CVD method (CCP-CVD), a photoCVD method, a plasma CVD method (PE-CVD), an epitaxial growth method, an atomic layer deposition (ALD) method, a reactive sputtering method, and other chemical vapor deposition methods.
[0263] Furthermore, the inorganic gas barrier layer can also be formed by coating a coating liquid containing an inorganic precursor such as polysilazane, tetraethyl orthosilicate (TEOS) on a support and then performing a modification treatment such as irradiation with vacuum ultraviolet light to form an inorganic gas barrier layer, or by film metallization technology such as plating a metal on a resin substrate to bond a metal foil to the resin substrate.
[0264] In addition, the inorganic gas barrier layer may include an organic layer containing an organic polymer. In other words, the inorganic gas barrier layer may be a laminate of an inorganic layer containing an inorganic material and an organic layer.
[0265] The organic layer can be formed, for example, by coating an organic monomer or an organic oligomer on a resin substrate to form a layer, followed by polymerization and crosslinking as required using, for example, an electron beam device, a UV light source, a discharge device or other appropriate device. Alternatively, it can be formed, for example, by evaporating an organic monomer or an organic oligomer that can flash evaporate and crosslink with radiation, and then forming a polymer from the organic monomer or organic oligomer. The coating efficiency can be improved by cooling the resin substrate.
[0266] As the coating method of organic monomer or organic oligomer, for example, roll coating (for example gravure roll coating), spray coating (for example electrostatic spray coating) etc. can be enumerated. In addition, as the example of the laminate of inorganic layer and organic layer, for example, the laminate of record in International Publication No. 2012 / 003198 and International Publication No. 2011 / 013341 etc. can be enumerated.
[0267] In the case of a laminate of an inorganic layer and an organic layer, the thickness of each layer may be the same or different. The thickness of the inorganic layer is preferably in the range of 3 to 1000 nm, more preferably in the range of 10 to 300 nm. The thickness of the organic layer is preferably in the range of 100 nm to 100 μm, more preferably in the range of 1 to 50 μm.
[0268] Example
[0269] The present invention is specifically described below with reference to examples, but the present invention is not limited thereto. It should be noted that in the following examples, unless otherwise specified, the operation is performed at room temperature (25° C.). In addition, unless otherwise specified, “%” and “parts” refer to “mass %” and “mass parts”, respectively.
[0270] [monomer]
[0271] The monomers used to prepare the encapsulating composition are as follows.
[0272] In addition, the dipole moment (μ), dispersion term (δD), polar term (δP), hydrogen bonding term (δH), and molecular volume (V) of each monomer are shown in the following table.
[0273] The dipole moment (μ) of each monomer was obtained from the chemical structure information of the monomer using Gaussian software manufactured by HULINKS Inc. In the calculation, PM6 of the semi-empirical method was used.
[0274] In addition, the hydrogen bonding term (δH) and molecular volume (V) of the monomers were calculated using the Hansen Solubility Parameters in Practice (HSPiP) software from the chemical structure information to obtain the δH (unit: MPa) of each monomer. 1 / 2 ) and V (unit: cm 3 ·mol -1 In addition, the dispersion term component δD and the polar term component δP (unit: MPa) are also obtained. 1 / 2 ).
[0275]
[0276]
[0277]
[0278]
[0279]
[0280]
[0281] [Table 1]
[0282]
[0283] [Table 2]
[0284]
[0285] [Preparation of Encapsulating Compositions 1 to 78]
[0286] Each monomer was weighed under a nitrogen atmosphere so as to have the type and mass fraction shown in Tables III to VI below.
[0287] Furthermore, 5 parts by mass of a phosphorus-based initiator (Omnirad 819 manufactured by IGM) as a photopolymerization initiator and 0.5 parts by mass of 2-isopropylthioxanthone (manufactured by Merck) as a sensitizer were placed in a brown bottle and stirred on a hot plate at 65° C. for 3 hours to obtain encapsulating compositions 1 to 78.
[0288] [Table 3]
[0289]
[0290] [Table 4]
[0291]
[0292] [Table 5]
[0293]
[0294] [Table 6]
[0295]
[0296] [S1 and S2]
[0297] The S1 and S2 in each encapsulating composition were calculated from the dipole moment (μ), dispersion term (δD), polar term (δP), hydrogen bonding term (δH) and molecular volume (V) of each monomer obtained above using the following formula, and are shown in the following table.
[0298] S1=(m1×μ1+m2×μ2+···) / (m1×V1+m2×V2+···)
[0299] S2=(m1×δH1+m2×δH2+···) / (m1×V1+m2×V2+···)
[0300] (In the above formula, m is the molar ratio of the monomer, and the suffixes of m, μ, V and δH are the numbers of the monomers)
[0301] The following table also shows the "average value (μ) [Debye] (m1×μ1+m2×μ2+···) of the dipole moment of each monomer in terms of molar ratio conversion", "average value (δH) [MPa 1 / 2 ](m1×δH1+m2×δH2+···)" and "the average value (V) [cm 3 ·mol -1](m1×V1+m2×V2+···)”.
[0302] [evaluate]
[0303] <Relative dielectric constant>
[0304] In a nitrogen environment, a coating film of the encapsulation composition having a thickness of 50 μm was prepared on a releasable film substrate having a size of 100 mm×100 mm. The coating film was heated at 300 mW / cm 2 The cumulative light intensity under the condition is 1.5mJ / cm 2 The coating was cured by irradiating ultraviolet light of a wavelength of 395 nm (MZ 240mm 395nm UVLED manufactured by IST). The cured film obtained was peeled off from the release film, and then a Ag film was formed on both sides by sputtering to prepare a measurement sample. The measurement sample was measured by impedance measurement using an impedance measurement device (Solartron 126096) at a frequency of 100 kHz and AC 0.1 (V) to measure the relative dielectric constant. A relative dielectric constant of 3.1 or less was qualified, and a case greater than 3.1 was unqualified.
[0305] <Inkjet ejection stability>
[0306] In a nitrogen environment, the encapsulation composition was filled into an inkjet head (KM1024i-MHE-D manufactured by Konica Minolta). The ink was ejected from the inkjet head at a frequency of 5 kHz, and 256 nozzles were observed. The presence or absence of droplet ejection and the volume of droplets during ejection from the 256 nozzles were observed, and the average, maximum, and minimum values of the volume were measured, and the volume change rate was calculated using the following formula.
[0307] Volume change rate = (maximum value - average value) ÷ average value × 100
[0308] or
[0309] Volume change rate = (average value - minimum value) ÷ average value × 100
[0310] Of the two volume change rates, the larger value is adopted.
[0311] The presence or absence of droplet discharge and the volume change rate were evaluated according to the following evaluation criteria. Levels 3 and 4 were considered acceptable.
[0312] (Evaluation Criteria)
[0313] Level 1: The number of nozzles that did not eject was 10 or more, or the number of nozzles that did not eject was less than 10 and the volume change rate was 20% or more
[0314] Level 2: The number of nozzles that did not eject was less than 10 and the volume change rate was 10% or more and less than 20%
[0315] Level 3: The number of nozzles that did not eject was less than 10 and the volume change rate was 5% or more and less than 10%
[0316] Level 4: The number of nozzles that are not ejected is less than 10 and the volume change rate is less than 5%
[0317] [Production of organic EL elements]
[0318] (1) Preparation of substrate
[0319] A 15 μm polyimide film was prepared as a film substrate, and a gas barrier layer for a film substrate (SiO2 film: 250 nm / SiNx film: 50 nm / SiO2 film: 500 nm (upper layer / middle layer / lower layer)) was formed on the polyimide film by plasma CVD.
[0320] (2) Formation of the first electrode
[0321] An Al film was formed as a first electrode (metal layer) on one surface of the substrate under the following conditions. The thickness of the formed first electrode was 150 nm. The thickness of the first electrode was a value measured by a contact-type surface profile measuring instrument (DECTAK).
[0322] The Al film was deposited using a vacuum evaporation device with a vacuum pressure of 1×10 -4 Pa was formed using a tungsten resistance heating crucible.
[0323] (3) Formation of organic EL layer
[0324] First, each evaporation crucible in a vacuum evaporation device is filled with the following materials constituting each layer of the organic functional layer in an amount optimal for producing each element. The evaporation crucible is made of a resistance heating material made of molybdenum or tungsten.
[0325] (3-1) Formation of Hole Injection Layer
[0326] Reduce the pressure to a vacuum degree of 1×10 -4 After Pa, the crucible for vapor deposition containing the following compound A-1 was energized and heated, and the compound A-1 was vapor deposited on the first electrode (metal layer side) at a vapor deposition rate of 0.1 nm / sec to form a hole injection layer with a thickness of 10 nm.
[0327] (3-2) Formation of hole transport layer
[0328] Next, the following compound M-2 was placed in a deposition crucible, which was energized and heated, and was deposited on the hole injection layer at a deposition rate of 0.1 nm / sec to form a hole transport layer with a thickness of 30 nm.
[0329] (3-3) Formation of Light Emitting Layer
[0330] Next, the following compound BD-1 and the following compound H-1 were co-deposited at a deposition rate of 0.1 nm / sec so that the concentration of compound BD-1 was 7 mass %, thereby forming a 15 nm thick light-emitting layer (fluorescent light-emitting layer) that emitted blue light.
[0331] Next, the following compounds GD-1, RD-1 and H-2 were co-deposited at a deposition rate of 0.1 nm / sec so that the concentrations of GD-1 and RD-1 were 20% by mass and 0.5% by mass, respectively, to form a yellow light-emitting layer (phosphorescent light-emitting layer) having a thickness of 15 nm.
[0332] (3-4) Formation of electron transport layer
[0333] Then, the heating boat containing the following compound T-1 as an electron transport material was energized to form an electron transport layer composed of Alq3 (tris(8-hydroxyquinoline)) on the light emitting layer. At this time, the deposition rate was set within the range of 0.1 to 0.2 nm / sec and the thickness was set to 30 nm.
[0334] (3-5) Formation of electron injection layer (metal affinity layer)
[0335] Next, the heating boat containing the following compound I-1 as an electron injection material was energized and heated to form an electron injection layer composed of Liq on the electron transport layer. At this time, the evaporation rate was set in the range of 0.01 to 0.02 nm / sec and the thickness was set to 2 nm. It should be noted that the electron injection layer functions as a metal affinity layer.
[0336] Through the above-mentioned operation, an organic EL layer emitting white light is formed.
[0337]
[0338] (4) Formation of the Second Electrode
[0339] Furthermore, a Mg / Ag mixture (Mg:Ag=1:9 (vol ratio)) was vapor-deposited to a thickness of 10 nm to form the extraction electrode as the second electrode.
[0340] (5) Formation of capping layer
[0341] Then, it was moved to the original vacuum chamber, and α-NPD (4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl) was vapor-deposited on the second electrode at a vapor deposition rate of 0.1 to 0.2 nm / sec until the thickness reached 40 nm, forming a covering layer for the purpose of improving light extraction.
[0342] (6) Formation of the first encapsulation layer
[0343] Next, as a first sealing layer covering the light-emitting portion of the organic EL element produced above, silicon nitride (SiNx, Vickers hardness HV900) was formed to a thickness of 500 nm by a plasma CVD method.
[0344] (7) Formation of the Second Encapsulation Layer
[0345] Next, the encapsulation composition 1 prepared above was filled into an inkjet head (KM1024i-MHE-D manufactured by Konica Minolta) under a nitrogen environment. Then, the encapsulation composition 1 was applied to the organic EL element formed up to the first encapsulation layer under a nitrogen environment using an inkjet method in a coating thickness of 10 μm. Then, the encapsulation composition 1 was applied at 300 mW / cm 2 The cumulative light intensity under the condition is 1.5J / cm 2 The second encapsulation layer is formed by irradiating ultraviolet light with a wavelength of 395 nm (MZ 240 mm 395 nm UV LED manufactured by IST).
[0346] (8) Formation of the third encapsulation layer
[0347] Next, silicon nitride (SiNx, Vickers hardness HV900) was formed as a third encapsulating layer with a thickness of 500 nm on the second encapsulating layer by a plasma CVD method, thereby obtaining an organic EL element 1 for evaluation having the first to third encapsulating layers formed thereon.
[0348] [Production of Organic EL Elements 2 to 78]
[0349] In the production of the organic EL element 1, organic EL elements 2 to 78 for evaluation were produced in the same manner except that the encapsulating composition 1 in forming the second encapsulating layer was changed as shown in the following table.
[0350] [evaluate]
[0351] <Luminescence characteristics (luminescence residual rate)>
[0352] Each organic EL element for evaluation was placed in a thermostatic chamber under a high temperature environment (temperature 85°C) and subjected to an accelerated degradation test. After 200 hours, each organic EL element was extracted from the thermostatic chamber and driven at a constant voltage at room temperature to emit light, and the luminous intensity was measured. The ratio (%) of the luminous intensity after the accelerated degradation test to the luminous intensity before the accelerated degradation test was measured and judged according to the following criteria. Levels 2 to 4 were considered qualified.
[0353] (Evaluation Criteria)
[0354] Level 1: Less than 80%
[0355] Level 2: 80% or more and less than 90%
[0356] Level 3: 90% or more and less than 95%
[0357] Level 4: 95% or more
[0358] <Crack resistance>
[0359] A 15 μm thick polyimide film was prepared as a film substrate, and a sealing layer was formed on the polyimide film by the same method as (6) Formation of the first sealing layer, (7) Formation of the second sealing layer, and (8) Formation of the third sealing layer to prepare an evaluation sample.
[0360] The evaluation sample was bent with a bending radius of R = 1.5 mm so that the polyimide film side became convex. It was fixed in the bent state and kept in an environment of -20°C for 24 hours. The evaluation sample was extracted and observed under a microscope for the presence or absence of cracks and film peeling, and judged according to the following evaluation criteria. Grades 2 to 4 were considered qualified.
[0361] (Evaluation Criteria)
[0362] Level 1: Film peeling occurs, or more than 10 cracks occur.
[0363] Level 2: No film peeling occurs, and the number of cracks is 5 or more but less than 10
[0364] Level 3: No film peeling occurs, and there are 2 or more to less than 5 cracks
[0365] Level 4: No film peeling and less than 2 cracks
[0366] [Table 7]
[0367]
[0368] [Table 8]
[0369]
[0370] [Table 9]
[0371]
[0372] [Table 10]
[0373]
[0374] As shown in the above results, the encapsulation composition of the present invention can form an encapsulation film having excellent ejection stability based on the inkjet method and a low relative dielectric constant compared to the encapsulation composition of the comparative example. Furthermore, it can be seen that the organic EL element encapsulated using the encapsulation composition of the present invention also has excellent luminescent properties and crack resistance.
[0375] Industrial Applicability
[0376] The present invention can be used for a composition for electronic device encapsulation, an electronic device encapsulation film, and a method for forming an electronic device encapsulation film, which can form an electronic device encapsulation film having excellent ejection stability, luminescence characteristics, and crack resistance by an inkjet method and a low relative dielectric constant.
Claims
1. A composition for encapsulating an electronic device, comprising a photopolymerizable monomer and a photopolymerization initiator, The photopolymerizable monomer includes (meth)acrylate, The following S1 calculated based on the dipole moment μ, molecular volume V and hydrogen bonding term δH of the photopolymerizable monomer is 0.10×10 -2 ~1.10×10 -2 Debye / (cm 3 ·mol -1 ) or the following S2 is within 0.50×10 -2 ~1.50×10 - 2 MPa 1 / 2 / (cm 3 ·mol -1 ), the unit of the dipole moment μ is Debye, and the unit of the molecular volume V is cm 3 ·mol -1 The unit of the hydrogen bond term δH is MPa 1 / 2 , S1=(m1×μ1+m2×μ2+···) / (m1×V1+m2×V2+···) S2=(m1×δH1+m2×δH2+···) / (m1×V1+m2×V2+···) In the formula, m is the molar ratio of the monomer, and the suffixes of m, μ, V and δH are the numbers of the monomers.
2. The composition for electronic device encapsulation according to claim 1, wherein The S1 is 0.50×10 -2 ~0.80×10 -2 Debye / (cm 3 ·mol -1 ) or the S2 is within the range of 0.50×10 -2 ~1.00×10 -2 MPa 1 / 2 / (cm 3 ·mol -1 ) within the range of .
3. The composition for electronic device encapsulation according to claim 1, wherein The hydrogen bond term δH is between 1.9 and 3.5 MPa. 1 / 2 within the range.
4. An electronic device packaging film is an electronic device packaging film for packaging electronic devices, having: a first encapsulation layer comprising silicon nitride, silicon oxide or silicon oxynitride, and A second encapsulating layer using the composition for encapsulating an electronic device according to any one of claims 1 to 3.
5. The electronic device packaging film according to claim 4, wherein: A third encapsulation layer including silicon nitride, silicon oxide or silicon oxynitride is provided on the second encapsulation layer.
6. A method for forming an electronic device encapsulating film, comprising: forming a first encapsulation layer on the electronic device by a vapor phase method, and A step of forming a second encapsulating layer by applying the electronic device encapsulating composition on the first encapsulating layer.
7. The method for forming an electronic device packaging film according to claim 6, wherein: The method further comprises forming a third encapsulating layer on the second encapsulating layer by a vapor phase method.
8. The method for forming an electronic device packaging film according to claim 6, wherein: The second encapsulation layer is formed by an inkjet method.